Theoretical observers for infinite dimensional skew-symmetric systems - DEGUENON, AYICHEOU JUDICAËL TCHEDJI; BĂRBULESCU, Alina (My University, 2019)
The observer construction has a main importance in the control theory and its applications for the systems of infinite dimension. Even if the system’ state has an infinite dimension, its estimation is given using some physical measures of finite dimensions. Considering unbounded boundary observations operators and assuming that the exact observability property holds, we build some Luenberger like observers which assure the exponential stability of the error system under some regularity conditions.
Keywords: observability; operator; regularity; stability